What if the elephant speaks? Kant's Critique of Judgment and an Übergang problem in John Hick's philosophy of religious pluralism - Seeman, Brad (International journal for philosophy of religion, 2003)
In the Critique of Judgment, Kantattempts to unravel the problem of Übergang that threatens his CopernicanRevolution. Having opened up a ``chasm'' betweensensible and supersensible, betweenepistemological and ontological, Kant facesboth the specter of empirical chaos in whichthe noumenal refuses to conform to theunderstanding's attempts to legislate over themanifold of intuition, and the problem offinding a place for freedom to have effectswithin the seamless phenomenal realm ofefficient causality. Central to Kant's attemptto overcome these problems is his notion of theheautonomy of reflective judging, in whichjudgment subjectively legislates its ownactivity. The net effect of this strategy isto preserve the integrity of the architectonicby permitting judgment use of ontologicalprinciples in regulating its own activity, butalways placing these ontological principlesunder an epistemological ``as if'' that cannot becarried over into the noumenal realm (e.g.,judgment can subjectively operate under theprinciple that the world appears ``as if'' it haspurpose, but this cannot be thought to apply tothe noumenal). Kant shields his architectonicby allowing it to encounter onlyepistemologically neutered noumena. This paperargues that Hick faces an analogousÜbergang problem, explores his``heautonomous'' attempt to blunt the problem,and concludes that the attempt fails, leavingHick with an unresolved problem of``onto-ethical discontinuity.''